PENGARUH MEDIA CANGKANG TELUR TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK WALDHA AL-ISLAMY PEKANBARU - Yesi Yuliana; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of eggshell media towards the fine motor skills of children aged 5-6 years in Childhood School Waldha Al-Islamy Pekanbaru. The research used experimental method with one group pre-test post-test design. The population in this study is B1 class children which amounted to 20 children and the sample in this study amounted to 20 children. The Data collection technique used in this study was using observation. The data analysis techniques used in this study using t test analysis. In hypothesis test in this research there is influence of eggshell media on fine motor ability of children aged 5-6 years in Childhood School Waldha Al-Islamy Pekanbaru. Obtained tcount of tcount = 11.533> t table = 2.093 with sig 0.000, because sig <0.05 it can be concluded that there is influence of eggshell media on fine motor ability in children. It can be interpreted that there is influence of eggshell media on fine motor ability of children aged 5-6 years in kindergarten Waldha Al-Islamy Pekanbaru significant equal to 76,92%.Keywords: Fine Motor Capability, Egg Shell Media